Inter-linkage among some physico-chemical and biological factors in the tropical mangrove estuary - Saifullah, A. S. M.; Mustafa Kamal, Abu Hena; Idris, Mohd Hanafi; Rajaee, Amy Halimah; Bhuiyan, Md. Khurshid Alam; Hoque, Mohammad Nesarul (Taylor & Francis, 2016)
The interaction between abiotic and biotic parameters in an ecosystem usually shows health and functioning of the system. Thus, some physico-chemical parameters, phytoplankton abundance, chlorophyll a and primary production of the mangrove estuary in Sarawak, Malaysia were extensively investigated from January 2013 to December 2013 in order to establish the inter-linkage among them. The Pearson correlation coefficient revealed a significant relation between atmospheric and water temperatures (r = 0.692). Similarly, surface water temperature showed a significant positive correlation with salinity (r = 0.744), TDS (r = 0.708) and conductivity (r = 0.776). The light extinction coefficient (LEC, K) changed negatively in relation to TDS (r =-0.623), conductivity (r =-0.644) and surface water temperature (r =-0.766). Ammonium showed a negative correlation with rainfall (r =-0.620) but a positive correlation with salinity (r = 0.600). The biological variable such as phytoplankton abundance was found to be positively correlated with chlorophyll a (r = 0.692), ammonium (r = 0.645) and silica (r = 0.644) and negatively with rainfall (r =-0.644). The canonical correspondence analysis revealed a strong positive correlation between environmental parameters and phytoplankton species. The analysis of variance disclosed significant seasonal differences in salinity, water temperature, TDS, conductivity, LEC, ammonium and chlorophyll a.